2009
DOI: 10.2134/agronj2009.0002
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Conventional versus Organic farming on Soil Carbon: Results from a 27‐Year Field Experiment

Abstract: Organic farming practices are regarded as being beneficial for the environment by promoting soil quality and sequestering soil organic carbon (SOC). We studied SOC dynamics in the long‐term field experiment DOK in Switzerland. The experiment compares three organically fertilized treatments under conventional (CONFYM), bioorganic (BIOORG), and biodynamic (BIODYN) management, and two systems with (CONMIN) or without (NOFERT) mineral fertilizer. We analyzed measured SOC time series from 1977 to 2004 and applied s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 43 publications
10
59
0
2
Order By: Relevance
“…Composted manure is typical for DYN, and, given that composting stabilizes organic matter such as raw manure, nominal equal C inputs may have differential effects on SOC. For the DOK experiment a loss of 21% C for 'conventional' manure versus 39% for composted manure prior to field application has been estimated (Leifeld et al 2009). Thus, the actual field balance without considering CO 2 produced off-site becomes biased.…”
Section: Discussion Factors Causing Differences In Socmentioning
confidence: 99%
See 4 more Smart Citations
“…Composted manure is typical for DYN, and, given that composting stabilizes organic matter such as raw manure, nominal equal C inputs may have differential effects on SOC. For the DOK experiment a loss of 21% C for 'conventional' manure versus 39% for composted manure prior to field application has been estimated (Leifeld et al 2009). Thus, the actual field balance without considering CO 2 produced off-site becomes biased.…”
Section: Discussion Factors Causing Differences In Socmentioning
confidence: 99%
“…In a paired t test, the difference in SOC content between DYN and ORG was significant. Only one experiment in a Californian vineyard showed no difference in SOC between ORG and DYN (Reeve et al 2005),whereas systematic differences were found in two controlled, long-term experiments at temperate sites in Germany (Raupp 2001) and Switzerland (Fließbach et al 2007, for lower fertilization level, and Leifeld et al 2009, for higher fertilization level). In the study of Raupp (2001), loss of SOC relative to CON was smaller in DYN than in ORG for low-and medium-level manure application and DYN was the only system that gained SOC under high organic fertilization.…”
Section: Discussion Factors Causing Differences In Socmentioning
confidence: 99%
See 3 more Smart Citations